Toward Paradigmatic Change in TESOL Methodologies: Building Plurilingual Pedagogies From the Ground Up. Issue 3 (16th August 2013) - Lin, Angel
<x xml:space="preserve">Abstract</x> Contemporary TESOL methodologies have been characterized by compartmentalization of languages in the classroom. However, recent years have seen the beginning signs of paradigmatic change in TESOL methodologies that indicate a move toward plurilingualism. In this article, the author draws on the case of Hong Kong to illustrate how, in the past four decades, deep‐rooted ideologies of linguistic purism combined with dominant TESOL knowledge claims have made it difficult to develop locally appropriate methodologies. She outlines the innovative work of some teachers who build up plurilingual pedagogies in content classrooms despite these difficulties, and on this basis proposes suggestions for future work.